Influence of peak ground acceleration and concrete grade on seismic design of RC hospital building - Ummu Nurulatiqah, Kamis (2019)
Nineteen miles below sea level in the early hours of December 26, 2004, a 9.1-magnitude earthquake shook the seas near the coast of Sumatra, in the northwestern reaches of the Indonesian archipelago. More than 227,000 people were declared dead or missing in the weeks after the tragedy that affected 14 countries across two continents. On June 5, 2015, a 5.9-magnitude earthquake rattled Sabah, killing 18 people on Mount Kinabalu. It was said to be the second powerful quake to hit Sabah after the 1976 earthquake measuring 6.2 on the Richter scale that occurred near Lahad Datu. The 2015 earthquake was felt across the state and more than 100 aftershocks were reportedly recorded throughout the year. Following the quake tragedy in Sabah, there have been concerns that an earthquake may also hit Peninsular Malaysia and according to a geological expert, such misgivings are not misplaced. The general perception has always been that Peninsular Malaysia was safe because we are far from the Pacific Ring of Fire which surrounds us, but in recent years, there is evidence of earthquakes with focal points or epicentres right under our feet, due to the reactivation of old fault lines. These fault lines seem to have been reactivated by active tectonic plate boundaries and this has caused a concern since many structures in the city were not built and designed to withstand earthquakes. The causes of the reactivation of fault lines in Malaysia is because it is surrounded by so many active tectonic plate boundaries and the Sunda Shelf, which the country sits on, is being compressed. Peninsular Malaysia is at the centre of the shelf, also known as Sundaland, which is absorbing all the stress from around it. Sooner or later, the earth has to find some release by breaking through old fault line systems. Due to this hazard effect, the structures need to be designed to resist the dynamic forces from the earthquakes. When the structure is designed to resist earthquake, the damage of the structure will not be too severe compared to the conventional structures. The effect of seismic design implementation on cost of materials is became an important topic to be investigated. In relation to that, this study discusses on the seismic design of 3 storey and 5 storey of reinforce concrete hospital building with consideration of different magnitude of Peak Ground Acceleration (PGA) and different grade of concrete. The objectives of this study are to determine the comparison on the amount of steel reinforcement required based on the two different parameters mentioned above compared to non-seismic design. Twelve models of hospital buildings with consideration of different PGA and concrete grade are considered. 6 models are used for magnitude of PGA equal to 0.08g along with concrete grade 25, and 6 other models are used for magnitude of PGA equal to 0.16g along with concrete grade 35. For different magnitude of PGA in 3 storey building, the results show that the percentage difference of steel reinforcement required compared to non-seismic design for beam and column of the whole building had increased from 44% to 156% for PGA equals to 0.08g and 0.16g respectively. While for different grade of concrete in 3 storey building, the results show that the percentage difference of steel reinforcement required compared to non-seismic design had decreased by 21% from concrete grade 25 to concrete grade 35 respectively.